Tryptophan-related dipeptides in fermented dairy products suppress microglial activation and prevent cognitive decline - Ano, Yasuhisa (Aging (Albany NY), 2019)
The rapid growth in aging populations has made prevention of age-related memory decline and dementia a high priority. Several epidemiological and clinical studies have concluded that fermented dairy products can help prevent cognitive decline; furthermore, intake of Camembert cheese prevents microglial inflammation and Alzheimer’s pathology in mouse models. To elucidate the molecular mechanisms underlying the preventive effects of fermented dairy products, we screened peptides from digested milk protein for their potential to regulate the activation of microglia. We identified dipeptides of tryptophan–tyrosine (WY) and tryptophan–methionine that suppressed the microglial inflammatory response and enhanced the phagocytosis of amyloid-β (Aβ). Various fermented dairy products and food materials contain the WY peptide. Orally administered WY peptide was smoothly absorbed into blood, delivered to the brain, and improved the cognitive decline induced by lipopolysaccharide via the suppression of inflammation. Intake of the WY peptide prevented microglial inflammation, hippocampal long-term potential deficit, and memory impairment in aged mice. In an Alzheimer’s model using 5×FAD mice, intake of the WY peptide also suppressed microglial inflammation and accumulation of Aβ, which improved cognitive decline. The identified dipeptides regulating microglial activity could potentially be used to prevent cognitive decline and dementia related to inflammation.